Compositional characteristics and hydration behavior of mineral trioxide aggregates - Wen-Hsi Wang; Chen-Ying Wang; Yow-Chyun Shyu; Cheing-Meei Liu; Feng-Huei Lin; Chun-Pin Lin (Elsevier, 2010)
Mineral trioxide aggregate (MTA) was one of most popular biomaterials for endodontic treatment in the past decade. Its superb biocompatibility, sealing ability and surface for tissue adhesion all make MTA a potential candidate for many dental applications, such as apexification, perforation repair, repair of root resorption, and as a root-end filling material. There are many review articles regarding the physical, chemical and biological properties of MTA. However, there are few reviews discussing the relationship between the composition and hydration behavior of MTA. The aim of this article was to provide a systematic review regarding the compositional characteristics and hydration behavior of MTA.